Princeton Readings in Religion and Violence - Juergensmeyer, Mark; Kitts, Margo, 1952- (Book collections on Project MUSE., 2011)
This groundbreaking anthology provides the most comprehensive overview for understanding the fascinating relationship between religion and violence--historically, culturally, and in the contemporary world. Bringing together writings from scholarly and religious traditions, it is the first volume to unite primary sources--justifications for violence from religious texts, theologians, and activists--with invaluable essays by authoritative scholars. The first half of the collection includes original source materials justifying violence from various religious perspectives: Hindu, Chinese, Christia.